PENGARUH PARTISIPASI ANGGARAN TERHADAP SENJANGAN ANGGARAN DENGAN LOCUS OF CONTROL DAN GOAL COMMITMENT SEBAGAI VARIABEL MODERATING (Studi Empiris di Pemerintahan Kota Pekanbaru) - Putri Dwi Nurhidayati; Nur Azlina; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aim to examine the influence of budgetary participation to budgetary slack with locus of control and goal commitment as moderated variables at (Empirical Study On Pekanbaru City Government). The data was collected by distributing questionnaires with purposive sampling to the respondents. While responders is consisted by the functional functionary aselon III and IV at governmental institution of Pekanbaru City which is participation in budgetary process, with a total sample are 93 respondents. The method analisys used in this study is multiple regression analysis with software SPSS for windows. From the results of multiple regression, there is three hypothesis that influent to budgetary slack : 1) the effect of budgetary participation having an effect on budgetary slack. 2) budgetary participation and locus of control interaction have significant influence to the budgetary slack. 3) budgetary participation and goal commitment interaction have significant influence to budgetary slack.Keywords: budget, participation, control, goal, and commitment